Plasma Levels of C-Type Lectin REG3α and Gut Damage in People With Human Immunodeficiency Virus. (23rd August 2019) - Isnard, Stéphane; Ramendra, Rayoun; Dupuy, Franck P; Lin, John; Fombuena, Brandon; Kokinov, Nikola; Kema, Ido; Jenabian, Mohammad-Ali; Lebouché, Bertrand; Costiniuk, Cecilia T; Ancuta, Petronela; Bernard, Nicole F; et al.
Abstract: Background: Regenerating islet-derived protein 3α (REG3α) is an antimicrobial peptide secreted by intestinal Paneth cells. Circulating REG3α has been identified as a gut damage marker in inflammatory bowel diseases. People living with human immunodeficiency virus (PWH) on antiretroviral therapy (ART) present with an abnormal intestinal landscape leading to microbial translocation, persistent inflammation, and development of non-AIDS comorbidities. Herein, we assessed REG3α as a marker of gut damage in PWH. Methods: Plasma from 169 adult PWH, including 30 elite controllers (ECs), and 30 human immunodeficiency virus (HIV)–uninfected controls were assessed. REG3α plasma levels were compared with HIV disease progression, epithelial gut damage, microbial translocation, and immune activation markers. Results: Cross-sectionally, REG3α levels were elevated in untreated and ART-treated PWH compared with controls. ECs also had elevated REG3α levels compared to controls. Longitudinally, REG3α levels increased in PWH without ART and decreased in those who initiated ART. REG3α levels were inversely associated with CD4 T-cell count and CD4:CD8 ratio, while positively correlated with HIV viral load in untreated participants, and with fungal product translocation and inflammatory markers in all PWH. Conclusions: Plasma REG3α levels were elevated in PWH, including ECs. The gut inflammatory marker REG3α may be used to evaluate therapeutic interventions and predict non-AIDS comorbidity risks in PWH.